1990
DOI: 10.18174/njas.v38i3b.16578
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of different techniques to assess the biological availability of feed phosphates in pig feeding.

Abstract: Piglets from about 6 weeks old were fed on basal diets with P 0, 0.6, 1.2 or 1.8 g/kg, 0, 1.2 or 2.2 g/kg, and 0 or 2.0 g/kg in experiments 1, 2 and 3, respectively. Blood factors did not show a significant response to P intake. Plasma alkaline phosphatase activity was not linearly related to P intake, while regressing the inorganic P content to the quantity of supplemented P resulted in a low fitness of the model (Rsuperscript 2 = 53%). Results from bone fat-free DM, concentration of ash in fat-free DM, amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 10 publications
3
18
0
1
Order By: Relevance
“…However, these experiments have also demonstrated that concentrations of AN phytase below 500 U/kg will not support adequate bone strength or P absorption (g/d) compared with pigs fed a PC diet containing supplemental inorganic P that meets the minimum aP requirements for swine (NRC, 1998). The differences in the sensitivity ranking of the response criteria in the current experiments and the experiments of Harper et al (1997) are in general agreement with other experiments that showed apparent total-tract absorption of P and bone measurements were more sensitive criteria than blood measurements or growth performance for estimating the bioavailability of P in swine diets (Koch et al, 1984;Dellaert et al, 1990;. Adequate bone strength is essential for market hogs that must be ambulatory when slaughtered, and for structural soundness of replacement gilts that enter the breeding herd.…”
Section: Discussionsupporting
confidence: 84%
“…However, these experiments have also demonstrated that concentrations of AN phytase below 500 U/kg will not support adequate bone strength or P absorption (g/d) compared with pigs fed a PC diet containing supplemental inorganic P that meets the minimum aP requirements for swine (NRC, 1998). The differences in the sensitivity ranking of the response criteria in the current experiments and the experiments of Harper et al (1997) are in general agreement with other experiments that showed apparent total-tract absorption of P and bone measurements were more sensitive criteria than blood measurements or growth performance for estimating the bioavailability of P in swine diets (Koch et al, 1984;Dellaert et al, 1990;. Adequate bone strength is essential for market hogs that must be ambulatory when slaughtered, and for structural soundness of replacement gilts that enter the breeding herd.…”
Section: Discussionsupporting
confidence: 84%
“…Last, we chose to focus on apparent P digestibility because we know of no data indicating that P is not digested in forms that are not fully available for utilization. This is supported by Ketaren et al (1993), who reported that percentages of apparent P digestibility and retention were similar for soybean meal when dietary P levels were below estimated requirements, and by Dellaert et al (1990), who reported that apparent P digestibility is one of the best measures to determine the nutritional value of feed phosphates. Additional discussion on P digestibility and phytase activity sites within the gastrointestinal tract have been described elsewhere (Jongbloed et al, 1992;Augspurger et al, 2003;Selle and Ravindran, 2008) and are beyond the scope of the current experiments.…”
Section: Animal Selection Diet Analysis and Phytase Analytical Methmentioning
confidence: 78%
“…Plasma iP increases with an increase in dietary P (Vipperman et al, 1974;Dellaert et al, 1990;Eeckhout et al, 1995) and, in general, with supplementation of dietary phytase (Lei et al, 1993a,b,c; Adeola et al, 1). The quadratic response is represented by the following equation: apparent P digestibility (%) = 15.80 + 0.0639 FTU − 0.0000335 FTU 2 (R 2 = 0.62).…”
Section: Plasma Ip and Phytasementioning
confidence: 99%
“…Pigs generally absorb more P than is utilized in metabolism (Finco, 1989), with excess P being excreted via urine or as endogenous P in feces. High levels of urinary P excretion are most often a result of excess dietary P (Poulsen, 2000), and urine P levels may be used as an indicator of adequate dietary P (Dellaert et al, 1990). Spencer et al (2000) showed elevated urine P with diets higher in available P due to formulation with HAP corn and supplemental inorganic P. Because the diets used in this experiment were considerably lower in available P than diets formulated to meet National Research Council P requirements, urine P values were considerably lower than would be expected for pigs under typical production conditions.…”
Section: Resultsmentioning
confidence: 99%